Bankruptcy Analysis of Companies Affected by the Boycott, Divestment, Sanctions (BDS) Movement - Jestica Arifani Dilla Hardanti; Heni Safitri; Dedi Hariyanto (IECON: International Economics and Business Conference, 2025)
This study sought to determine the outcomes of corporate bankruptcy predictions using the Springate, Zmijewski, and Grover models on companies impacted by the Israeli Boycott, Divestment, Sanctions (BDS) Movement. The study's population consisted of 22 companies affected by the Israeli BDS Movement operating within Indonesia. A total sampling technique was employed, including all 22 companies. The analysis utilized three distinct models Springate, Zmijewski, and Grover to predict corporate bankruptcy. The analysis of bankruptcy predictions yielded the following results: the Springate model predicted 12 companies would experience bankruptcy, with 10 not at risk. The Zmijewski model identified 6 companies as potentially bankrupt and 16 as not at risk. The Grover model predicted 5 companies would experience bankruptcy and 17 would not. Overall, the combined analysis of the three models identified 3 companies that were predicted to experience bankruptcy and 8 companies that were not.